Rapid Assessment of Reward‐Related Eating: The RED‐X5. Issue 2 (24th January 2019) - Vainik, Uku; Eun Han, Jung; Epel, Elissa S.; Janet Tomiyama, A.; Dagher, Alain; Mason, Ashley E.
Abstract : Objective: The prevalence of obesity has created a plethora of questionnaires characterizing psychological aspects of eating behavior, such as reward‐related eating (RRE). The Reward‐based Eating Drive questionnaires (RED‐9, RED‐13) broadly and deeply assess the RRE construct. However, large‐sample research designs require shorter questionnaires that capture RRE quickly and precisely. This study sought to develop a brief, reliable, and valid version of the RED questionnaire. Methods: All‐subset correlation was used to find a subset that maximally associated with the full RED‐13 in two separate samples. Results were validated in a third independent sample. Internal consistency, test‐retest reliability, and ability to explain variance in external outcomes were also assessed. Results: A five‐item questionnaire (RED‐X5) correlated strongly with RED‐13 in the independent sample ( r  = 0.95). RED‐X5 demonstrated high internal consistency (omega total ≥ 0.80) and 6‐month test‐retest reliability ( r  = 0.72). RED‐X5 accurately reproduced known associations between RED‐13 and BMI, diabetes status, and craving for sweet and savory foods. As a novel finding, RED questionnaires predicted laboratory intake of chips. Conclusions: RED‐X5 is a short, reliable, and valid measure of the RRE construct and can be readily implemented in large‐sample research designs in which questionnaire space is limited.